2020
DOI: 10.1016/j.fishres.2020.105614
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography and population dynamics of the Eastern Mediterranean whiting (Merlangius merlangus) from the Black Sea, the Turkish Straits System, and the North Aegean Sea

Abstract: In this study, the taxonomic resolution and phylogenetic relationship of two presumed subspecies of Merlangius merlangus, namely M. m. euxinus and M. m. merlangus, were investigated. In addition, the effect of the Turkish Straits System on the evolutionary history and genetic structure of M. merlangus, was explored. The mitochondrial cytochrome c oxidase subunit 1 and cytochrome b genes, and the nuclear recombination activating gene-1 were analysed. Our results indicate no clear distinction between the two pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Previous studies, based on morphological and meristic features, revealed differentiation between the AS and the Black Sea, raising a debate about the existence of two subspecies [93,94]. Recent molecular analyses have attempted to answer this question, stating that, despite some genetic differentiation between different sampling sites in the Black and Aegean Seas, there is no evidence supporting the existence of the presumed subspecies [95].…”
Section: Population Biological Traitsmentioning
confidence: 99%
“…Previous studies, based on morphological and meristic features, revealed differentiation between the AS and the Black Sea, raising a debate about the existence of two subspecies [93,94]. Recent molecular analyses have attempted to answer this question, stating that, despite some genetic differentiation between different sampling sites in the Black and Aegean Seas, there is no evidence supporting the existence of the presumed subspecies [95].…”
Section: Population Biological Traitsmentioning
confidence: 99%
“…During the definitive identification of a species, classical morphological characters can be misleading due to the existence of these changes over time (Menon, 1989;Ganai et al, 2014). For this reason, comparisons based on morphological characters are not sufficient for taxonomists to make the right decision for determining the species (Hua et al, 2019;Şalcıoğlu et al, 2020). Proteins are used as genetic markers that play an important role in determining taxonomic relationships (Crick, 1963;Nirenberg et al, 1963;Ochoa, 1963;Ganai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%